Power Density Case Study for 5G mmWave Array Antennas. (9th June 2021) - Qi, Dianyuan; Zou, Fangzhu; Zhao, Jing; Sun, Shaobin; Wei, Huanbin; Chen, Yiling; Xia, Zhan
Abstract : As 5G millimeter wave (mmWave) wireless device involves some new technologies, such as beamforming, the radiofrequency (RF) exposure compliance test for the 5G mmWave wireless device is significantly complicated. In order to shorten the compliance period for 5G mmWave terminals, the relevant regulatory authorities recommend a combination of numerical simulation and measurements to demonstrate compliance. To verify the feasibility of this method, the RF exposure test conducted in this paper was a reverse procedure according to IEEE (the Institute of Electrical and Electronics Engineers) standards. First, actual measurements under various conditions, including different beam configurations, different test distances, different input power levels, different duty cycle, and nonpeak directions, were performed, and the changing trend of PD over testing conditions was analyzed. Then one dual-polarized patch antenna array was selected for simulation analysis. The feasibility of the method proposed in IEEE standards was proved through the comparison of the results experiment and numerical analysis.